Evaluating the Dissent in State of Oregon v. Ashcroft: Implications for the Patient-Physician Relationship and the Democratic Process - Hilliard, Bryan (The Journal of law, medicine & ethics, 2005)
Over the past decade or so, no issue in medical ethics or bioethics law has raised more concerns about federal intervention in the practice of medicine, about judicial attempts to craft health policy, or about the wisdom of public mandates directing specific health care initiatives than the issue of physician-assisted suicide. State voter referenda, lower and federal court cases (including two U.S. Supreme Court decisions), proposed legislation in both houses of Congress, and orders and determinations from agencies within the executive branch of two administrations are representative of the kinds of actions taken in the last ten years implicating medical care at the end of life. Whether the intent was to codify into law physician-assisted suicide, to deny a constitutional right of assisted suicide, or to make “easier” physicians' efforts to alleviate intractable suffering at the risk of hastening death, or to prohibit physician aid in dying altogether, the impact on the patient-doctor relationship and on our understanding of what constitutes dignified and humane care at the end of life is undeniable.